Changes Over Time in the Global Multidimensional Poverty Index: A Ten-Country Study - Alkire, S; Kovesdi, F; Mitchell, C; Pinilla-Roncancio, M; Scharlin-Pettee, S (Oxford Poverty and Human Development Initiative (OPHI), 2019)
This brief methodological note presents a ten-country study of changes over time in multidimensional poverty, using the 2019 global MPI specifications. 1 Accompanying tables release the full results in these categories: national, rural, urban, subnational regions, age groups and complete estimations, as well as complementary data, indicator breakdowns, and standard errors. This note first explains the choice of the ten countries for this preliminary study of changes over time. It then describes the principles used to guide the data harmonisation process and the estimation procedures. Then, it provides the methodological details of harmonisation for the estimation of each dataset used. The results of these estimations are presented in Table 6, available online